Documents on History of Russian Naval Emigration in Regional Archives of Southern France: Problems of Search and Study - M. M. Rudkovskaya (Научный диалог, 2021)
The article deals with the problem of identifying, describing and introducing into scientific circulation documents and materials on the history of the Russian naval officers who lived in the region of southern France in the 1920s—1930s. The relevance and novelty of the research is due to the introduction into scientific circulation of documentary complexes of regional, local and departmental archives containing information about the Russian naval emigration in France. The author draws attention to the specifics of identifying archival documents within the framework of the research topic. Attention is paid to the peculiarities of the collection of funds in the French archives. It is shown how knowledge of this specificity makes it possible to find and identify the required materials in the absence of thematic collections and indexes. The results of a study of archival collections and funds discovered by the author in regional, local and departmental archives containing information about the history of the Russian naval emigration in southern France are presented in the article. Contrary to the ideas of the marginality of this topic that have developed in French historiography, the potential of its development on the basis of the materials identified by the author is demonstrated. A review of the discovered archival funds is carried out from the point of view of the prospects for the reconstruction of collective and individual biographies of Russian naval officers-emigrants. The author’s classification of the identified documentary complexes is proposed.